Home Monitoring of Heart Rate as a Predictor of Imminent Cardiovascular Events - Tulppo, Mikko P.; Kiviniemi, Antti M.; Junttila, M. Juhani; Huikuri, Heikki V. (Frontiers in Physiology, 2019)
Introduction: Previous studies have documented that day-to-day variability of heart rate (HR) has prognostic significance for cardiovascular (CV) events in general population. It is unknown how HR dynamics variate before imminent CV event in patients with coronary artery disease (CAD). Our aim was to study day-to-day variation in HR dynamics before the occurrence of CV event in patients with initially stable CAD. Methods: Forty-four patients with angiographically documented CAD from ARTEMIS study measured R-R intervals on a weekly basis at home for two years. Home measurements were performed in controlled conditions (3 min at supine and sitting) 1-2 times per week. Eleven patients had a CV event (7 acute coronary syndromes, 1 cardiac death, 2 new onset of arrhythmia needing hospitalization and 1 stroke), which occurred 11±7 months after enrolment. Mean R-R interval was analyzed prospectively from the home measurements. For the patients with new CV event, average and standard deviation (SD) of the mean R-R interval over 8 weeks preceding the CV event were calculated. For the patients without new CV event, corresponding period was determined by the median follow-up at the occurrence of new CV event. Results: There were no differences in the mean R-R interval analyzed over 8 weeks between the patients with and without new CV event. The variability of mean R-R interval over 8 weeks was greater in the patients with new CV event compared to the patients without new CV event at the supine (95±34 vs. 59±26 ms, p<0.001) and sitting positions (92±28 vs. 62±24 ms, p<0.001). Conclusions: Day-to-day variability of mean R-R interval is greater before the new CV event in CAD patients suggesting to a more unstable cardiac autonomic regulation preceding these events.